Tren Penelitian Augmented Reality dalam Pembelajaran Biologi: Sistematik Literatur Review dari 2020-2024 - Indrati, Dika Agustia; Masing, Feliksitas Angel (Universitas Negeri Jakarta, 2025)
This study is a systematic literature review (SLR). The purpose of this study is to determine research trends related to the use of augmented reality (AR) in biology learning from 2020 to 2024. The method used is the PRISMA method. The database used for article searches is Google Scholar. The keywords used in the article search are